1983
DOI: 10.1002/ajpa.1330610107
|View full text |Cite
|
Sign up to set email alerts
|

Volume and composition of hand sweat of white and black men and women in desert walks

Abstract: Many investigators have sought, but failed to find, ethnic differences in the number and regional distribution of active sweat glands. In this study measurements have been made of sweat secreted on one hand and also on the whole body of Whites and Blacks walking in desert heat. Whites numbered 31 men and 27 women, ages 30 to 88 years; there were 21 Black men and 31 Black women, ages 16 to 61 years. Each walked on three occasions for 1 hour at a rate that required an oxygen consumption of about 40% of aerobic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Racial differences in sweat K have not been well studied; a study of hand sweat of white and black individuals who walked in a desert did not reveal a racial difference in sweat K concentration, but the volume of hand sweat (which has a higher concentration of K than body sweat) was higher, not lower, in white than in black individuals. 28 Black-white differences in stool excretion could possibly account for racial differences in urinary K excretion, but this has also not been well studied. In two small studies (one in South Africa and one in the United States), urinary and stool K excretion were both higher in white than in black individuals on uncontrolled diets, but the ratio of fecal to urinary K was higher in black than in white individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Racial differences in sweat K have not been well studied; a study of hand sweat of white and black individuals who walked in a desert did not reveal a racial difference in sweat K concentration, but the volume of hand sweat (which has a higher concentration of K than body sweat) was higher, not lower, in white than in black individuals. 28 Black-white differences in stool excretion could possibly account for racial differences in urinary K excretion, but this has also not been well studied. In two small studies (one in South Africa and one in the United States), urinary and stool K excretion were both higher in white than in black individuals on uncontrolled diets, but the ratio of fecal to urinary K was higher in black than in white individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Aloia has shown that black women have greater total body Na þ content and that the excess body Na þ compared with White women is localized to skeletal tissue [38]. Finally, it should be noted that there is no racial difference in the loss of K þ by sweat [27,39].…”
Section: Discussionmentioning
confidence: 95%
“…Second, in humans, sweat glands contribute up to 50% of total salt and water excretion during extensive exercise and psychoemotional activity [9]. Third, in a hot environment, the function of sweat glands is suppressed in Blacks compared to Whites [10]. Fourth, salt retention by sweat glands results in augmented salt-loading of renal distal tubules, which in turn leads to apical membrane depolarization and enhanced K þ secretion [11].…”
mentioning
confidence: 97%